2012
DOI: 10.1177/039463201202500125
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Loratadine Syrup and Cyproheptadine HCL Solution for Treating Perennial Allergic Rhinitis in Taiwanese Children Aged 2–12 Years

Abstract: We assessed the efficacy of loratadine syrup compared with cyproheptadine HCl solution for treating children aged from 2 to 12 years with perennial allergic rhinitis (PAR) in Taiwan. Sixty children with mite-induced PAR were enrolled and randomly placed into two treatment groups: loratadine syrup or cyproheptadine HCl solution. Treatment efficacy and symptom changes from baseline to post-treatment were evaluated by total symptom scores and visual analogue scales (VAS) during a 2-week period. There were no diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
(19 reference statements)
0
19
0
Order By: Relevance
“…Thermal analyses data reveal that compounds 1-6 and 8 are hydrated, having a weight loss between 100 and 211 o C which corresponds to one molecule (1,3,4,6,8) or two molecules (2, 5) of water respectively directly bonded to the metal center. The second weight loss steps correspond to the release of small coordinated anions: OAc -, Cl -, ClO 4 -.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal analyses data reveal that compounds 1-6 and 8 are hydrated, having a weight loss between 100 and 211 o C which corresponds to one molecule (1,3,4,6,8) or two molecules (2, 5) of water respectively directly bonded to the metal center. The second weight loss steps correspond to the release of small coordinated anions: OAc -, Cl -, ClO 4 -.…”
Section: Resultsmentioning
confidence: 99%
“…The tricyclic framework of 5H-dibenzo[a,d] [7]annulene constitutes an integral part of the structure of molecules that are known to be effective for the treatment of depressive disorders [1,2]. Analogs of 5H-dibenzo[a,d] [7]annulene, such as Protriptyline and Demexiptyline, are well known tricyclic antidepressants [3]. Dibenzo [a,d] [7]annulene derivatives exhibit antidiabetic, antiparasitic, metalloprotease inhibitors, antihypertensive, orexygenic and antimicrobial activity [4,5].…”
mentioning
confidence: 99%
“…Small prospective studies evaluated cyproheptadine in children with allergic conditions, including primary acquired cold urticaria26 and mite-induced allergic rhinitis 27. In each of these trials, the active comparator (ketotifen and loratadine, respectively) showed similar or better results when compared with cyproheptadine (table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Up to 30-fold overdoses of loratadine have not been causally associated with serious adverse events or fatality. A study by Wu et al (2012) comparing the efficacy of treatment for persistent allergic rhinitis (PAR) in children 2-12 years old of loratadine syrup formulation and cyproheptadine solution described a significantly reduced total symptom score with an improvement in side effects involving the central nervous system in the loratadine group. In the Preventia I study, well tolerated long term safety effects were described in the 12-30 months of age group during Phase I studies.…”
Section: Loratadine and Desloratadinementioning
confidence: 99%